The Concept of Religious Moderation From Sunan Kudus' Perspective and Its Correlation with Islamic Education in The Modern Era - Mujtahid, Mujtahid; Assidiqi, Ali Hasan; Sadiyah, Dini (Al Ulya: Jurnal Pendidikan Islam, 2025)
This research is motivated by the many cases of Intolerance, violence, riots, terror against religious leaders, hoax news, hate speech, provocative issues, in the name of religion, being a source of hostility both between people and groups. This research aims to discuss the concept of religious moderation of Sunan Kudus and its implementation. The study used is a type of literature with a descriptive analysis approach. The results show that Sunan Kudus teaches religious moderation in da'wah and his daily journey by adjusting most people's beliefs. Sunan Kudus also teaches respect and the absence of violence, but harmony. The correlation with the modern era is that it does not interfere with or be hostile to different people. Religion teaches many values to coexist, as Sunan Kudus's message. Even traditions that exist to this day, such as gusjigang in the holy society, teach to have good morals, trade honestly, and respect fellow human beings even though they are different and enjoy togetherness by helping each other instead of following the teachings of jihad and terrorism that are hostile to others.